Real-time imaging of senescence in tumors with DNA damage - Wang, Ying; Liu, Jun; Ma, Xiaowei; Cui, Chao; Deenik, Philip R.; Henderson, Paul K. P.; Sigler, Ashton L.; Cui, Lina (Scientific reports, 2019)
Detection of cellular senescence is important not only in the study of senescence in various biological systems, but also in various practical applications such as image-guided surgical removal of senescent cells, as well as the monitoring of drug-responsiveness during cancer therapies. Due to the lack of suitable imaging probes for senescence detection, particularly in living subjects, we have developed an activatable near-infrared (NIR) molecular probe with far-red excitation, NIR emission, and high “turn-on” ratio upon senescence-associated β-galactosidase (SABG) activation. We present here the first successful demonstration of NIR imaging of DNA damage-induced senescence both in vitro and in human tumor xenograft models.